a+3b=-2

Simple and best practice solution for a+3b=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+3b=-2 equation:


Simplifying
a + 3b = -2

Solving
a + 3b = -2

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3b' to each side of the equation.
a + 3b + -3b = -2 + -3b

Combine like terms: 3b + -3b = 0
a + 0 = -2 + -3b
a = -2 + -3b

Simplifying
a = -2 + -3b

See similar equations:

| 7(y-6)=28 | | 5.6+10.5=2.1A | | 8x^2+22x=-5 | | 11x-20=7x-64 | | -(1-7x)-6(-7-x)=36 | | 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 | | -8x-9x=.66 | | 2a=18 | | 12=x^2-6x | | 3x+9-x=15 | | 36x^2-9x=0 | | 10x^2-8x+1=0 | | 10x^2=58 | | 19x^2=58 | | 24a-22=-49(1-6a) | | 3x+11=-1 | | 16x-3=102-5x | | 107-14-6y=-2(y-4y) | | 60-2x+70-4x=180 | | 4/5/10/6= | | h=3+65t-16t^2 | | h=-16t^2+65t+3 | | -35=-7(5p-5)-5(4p+3) | | -52=-8(4-5n)-4(n-4) | | -1+x^2-1x=0 | | 4(-7+2m)+4(1-m)=-36 | | (80-x)+(90-2x)=180 | | x^2-x=23 |

Equations solver categories